Effects of an aquatic protocol on electromyography activation and strength of lower limb muscles in blind women: A randomized controlled trial - Asma Salari; Mansour Sahebozamani; Abdolhamid Daneshjoo; Mohammad Alimoradi; Mojtaba Iranmanesh; Nicola Relph; Guillermo Mendez-Rebolledo (PLoS ONE, 2025)
Purpose Visual impairment poses considerable challenges to mobility and everyday tasks, frequently leading to a more sedentary lifestyle and reduced physical fitness levels. Therefore, this study investigated the effects of a tailored aquatic exercise protocol on muscle activation and strength in visually impaired individuals. Materials and methods Thirty women who were blind (mean age = 29.03 ± 2.20 years) were randomly assigned to an experimental (EX) group and a control (CO) group. The EX group participated in three weekly 60-minute aquatic sessions, while the CO group maintained regular activities. Electromyography (EMG) activation and onset time were measured in the tibialis anterior, gastrocnemius medialis, rectus femoris, and biceps femoris. Muscle strength was also assessed in the ankle dorsiflexors and plantarflexors, as well as the knee flexors and extensors. Results The EX group showed increased EMG activation for the tibialis anterior, gastrocnemius medialis, rectus femoris, and biceps femoris in both anterior-posterior (2.23 MVIC%, 95% CI: 1.13 to 3.34, p < 0.001) and posterior-anterior directions (2.35 MVIC%, 95% CI: 1.80 to 2.91, p < 0.001) compared to CO group. Onset time decreased significantly in the EX group relative to CO group (anterior-posterior: -108.07 ms, 95% CI: -117.23 to -98.89, p < 0.001; posterior-anterior: -98.72 ms, 95% CI: -106.54 to -90.90, p < 0.001). Muscle strength significantly increased in the EX group compared to the CO group, with greater strength in ankle dorsiflexors (4.42 N/kg, 95% CI: 3.42 to 5.42, p < 0.001) and knee extensors (2.72 N/kg, 95% CI: 1.04 to 4.40, p < 0.001). Conclusions The aquatic exercise program improved neuromuscular function and strength in women with visual impairments, supporting its use in rehabilitation. Trial registration IRCT2017022132705N1